National Geographic angry birds : 50 true stories of the fed up, feathered, and furious - White, Mel. (Washington, D.C. : National Geographic, 2012)
Profiles real-world angry birds, with humorous stories and tips to avoid them, and includes facts about angry bird behavior.
Young Adult.
Young Adult
Keywords: Bird watching -- Humor; Birds -- Humor; Bird watching -- Humor; Birds -- Humor; HUMOR / General; NATURE / Birdwatching Guides; NATURE / General